Assembly and comparative analysis of the complete mitochondrial genome of Salix wilsonii using PacBio HiFi sequencing - Han, Fuchuan; Qu, Yanshu; Chen, Yicun; Xu, Li’an; Bi, Changwei (Frontiers in Plant Science, 2022)
Salix L. (willows) is one of the most taxonomically complex genera of flowering plants, including shrubs, tall trees, bushes, and prostrate plants. Despite the high species diversity, only five mitochondrial genomes (mitogenomes) have been released in this genus. Salix wilsonii is an important ornamental and economic willow tree in section Wilsonia of the genus Salix. In this study, the S. wilsonii mitogenome was assembled into a typical circular structure with a size of 711,456 bp using PacBio HiFi sequencing. A total of 58 genes were annotated in the S. wilsonii mitogenome, including 33 protein-coding genes (PCGs), 22 tRNAs, and 3 rRNAs. In the S. wilsonii mitogenome, four genes (mttB, nad3, nad4, and sdh4) were found to play important roles in its evolution through selection pressure analysis. Collinearity analysis of six Salix mitogenomes revealed high structural variability. To determine the evolutionary position of S. wilsonii, we conducted a phylogenetic analysis of the mitogenomes of S. wilsonii and 12 other species in the order Malpighiales. Results strongly supported the segregation of S. wilsonii and other five Salix species with 100% bootstrap support. The comparative analysis of the S. wilsonii mitogenome not only sheds light on the functional and structural features of S. wilsonii but also provides essential information for genetic studies of the genus Salix.